Beyond Park Boundaries: Exploring The Effect of Surrounding Land Use on Sound Levels of Parks - Lee, Josephine Siaw Ling; Hosni, Nafisa; Rusli, Noradila; Ghani, Nabila Abdul (Geoplanning: Journal of Geomatics and Planning, 2024)
Urban parks in big cities can help reduce noise while providing spaces for recreation and rest, but their size, location and surroundings can limit their environmental benefits. This article will discuss how surrounding land use affects noise levels in a particular park, as well as how park landscaping can limit noise exposure. Four study areas were selected from Kuala Lumpur and Putrajaya to highlight a range of land uses, locations and park sizes. The sound levels were measured twice for each site-morning and evening-using measurement points along the park path and the SL-5868P sound level meter. The results showed that the study area exceeded the recommended noise limit of 55dBA as stipulated by Malaysian Noise Limit and World Health Organization guidelines. In addition, there was a pattern of influence on the measured noise levels based on land use and landscape around the park. Parks located in dense land use have higher noise levels, but have lower variation in noise levels within the park due to higher surrounding noise levels, compared to parks with more than 87% tree cover. The KLCC park, with 76% tree cover, has an overall higher noise level of more than 60dBA, indicating that the tree cover serves as a noise barrier for the park. Therefore, park planning should be tailored to its location and environment, while landscaping can be used to reduce noise levels and keep them within noise limits. In the future, the soundscape idea may be taken into account to enhance Malaysia's park environment.